Examining the Relationship Between Teachers’ ICT Self-Efficacy for Educational Purposes, Collegial Collaboration, Lack of Facilitation and the Use of ICT in Teaching Practice - Hatlevik, Ida K.R.; Hatlevik, Ove E. (Frontiers in Psychology, 2018)
Information and communication technology (ICT) is now an integrated and central element of modern life, and its rapid emergence is changing the execution and organisation of work and learning. Digital technology is also important for schools, and hence for teachers’ working days. However, among today’s teachers, not everyone has the knowledge required to teach using digital technology. Recent research indicates that self-efficacy is important for how teachers master their practice. This paper addresses teachers’ ICT self-efficacy for educational purposes, and examines the assumed antecedents of teachers’ self-efficacy. Data from 1,158 teachers at 116 Norwegian schools was analysed. The results indicate that teachers’ self-efficacy for using ICT in their teaching practice is associated with their use of ICT in teaching and their general ICT self-efficacy. In addition, the results show that collegial collaboration among teachers has a positive association with the use of ICT in their teaching practice. One interpretation of these findings is that general ICT self-efficacy is necessary for developing ICT self-efficacy for educational purposes and being able to use ICT in education. However, further research is required to scrutinise the relationships between these concepts.